Using sporting migrants to build secondary sport: a 12 year case study of Czech basketball - William Crossan; Ondřej Pecha (Karolinum Press, 2016)
This study examines the effects of the sport migration that occurred over a 12 year period in the secondary sport of basketball in the Czech Republic, in terms of its effect on the popularity of the sport within the culture. The factors of fan attendance and youth membership are isolated and measured quantitatively, using multi-level analysis within teams, between teams and at a federation level. The study was carried out in order to measure the effect of the use of immigrant athletes from an individual team management perspective and from a league growth perspective. It was found that while foreigners displace national athletes, fans were attracted to the use of foreigners and youth were attracted to play the game. The use of foreigners had the most significant correlations at the between team level to home attendance and final placement in the league. Multi-level analysis was used to show that the use of foreigners can be a facilitator for federations and team management to build the popularity of secondary sports in a culture, with certain limitations. This quantitative study of a secondary sport is an addition to the majority of the literature on sport migration, which has been largely conducted on primary sports from a qualitative, sociological perspective.